EARLY DETECTION OSTEOPOROSIS RISK FACTORS OF WOMEN AGE MORE THAN 50 YEARS IN KOTA GORONTALO - Sri Ibrahim; Dewi Suryaningsih (Universitas Negeri Gorontalo, 2022)
Osteoporosis is a disease characterized by a decrease in bone density and disruption of normal bone architecture. Decreased bone strength increases the risk of fracture. The World Health Organization (WHO) includes osteoporosis in the list of 10 major degenerative diseases in the world. It is noted that there are approximately 200 million patients worldwide who suffer from osteoporosis. From the report of the Indonesian osteoporosis association, as many as 41.8% of men and 90% of women already have symptoms of osteoporosis. One of the efforts to reduce the incidence of osteoporosis is by early detection and avoiding risk factors for osteoporosis. This study aims to determine the risk factors for osteoporosis in women over 50 years. The research subjects were women over 50 years old in Gorontalo City. This study used a descriptive design by collecting questionnaires for early detection of osteoporosis risk factors including age, history of fracture, early menopause, family history of disease, corticosteroid consumption, physical activity, alcohol consumption, and smoking habits. The results of the identification of risk factors related to the incidence of osteoporosis were found at the age of 51-61 years as many as 169 people (70.1%), age 66 years as many as 72 people (29.9%), family history of osteoporosis as many as 44 people (18.3 %), history of fracture as many as 18 people (7.5%), history of taking steroids as many as 65 people (27.0%), alcohol consumption as many as 7 people (2.9%), smoking habits as many as 13 people (5.4% ), irregular in exercising as many as 142 people (58.9%), diabetes mellitus as many as 69 people (28.6%), hypertension as many as 5 people (2.1%), and hyperthyroidism as many as 4 people (1.6% ). Therefore, it is necessary to take preventive action by modifying these risk factors.